Elucidating the picocyanobacteria salinity divide through ecogenomics of new freshwater isolates - Pedro J. Cabello-Yeves; Cristiana Callieri; Antonio Picazo; Lena Schallenberg; Paula Huber; Juan J. Roda-Garcia; Maciej Bartosiewicz; Olga I. Belykh; Irina V. Tikhonova; Alberto Torcello-Requena; Paula Martin De Prado; Richard J. Puxty; et al. (BMC Biology, 2022)
Abstract Background Cyanobacteria are the major prokaryotic primary producers occupying a range of aquatic habitats worldwide that differ in levels of salinity, making them a group of interest to study one of the major unresolved conundrums in aquatic microbiology which is what distinguishes a marine microbe from a freshwater one? We address this question using ecogenomics of a group of picocyanobacteria (cluster 5) that have recently evolved to inhabit geographically disparate salinity niches. Our analysis is made possible by the sequencing of 58 new genomes from freshwater representatives of this group that are presented here, representing a 6-fold increase in the available genomic data. Results Overall, freshwater strains had larger genomes (≈2.9 Mb) and %GC content (≈64%) compared to brackish (2.69 Mb and 64%) and marine (2.5 Mb and 58.5%) isolates. Genomic novelties/differences across the salinity divide highlighted acidic proteomes and specific salt adaptation pathways in marine isolates (e.g., osmolytes/compatible solutes - glycine betaine/ggp/gpg/gmg clusters and glycerolipids glpK/glpA), while freshwater strains possessed distinct ion/potassium channels, permeases (aquaporin Z), fatty acid desaturases, and more neutral/basic proteomes. Sulfur, nitrogen, phosphorus, carbon (photosynthesis), or stress tolerance metabolism while showing distinct genomic footprints between habitats, e.g., different types of transporters, did not obviously translate into major functionality differences between environments. Brackish microbes show a mixture of marine (salt adaptation pathways) and freshwater features, highlighting their transitional nature. Conclusions The plethora of freshwater isolates provided here, in terms of trophic status preference and genetic diversity, exemplifies their ability to colonize ecologically diverse waters across the globe. Moreover, a trend towards larger and more flexible/adaptive genomes in freshwater picocyanobacteria may hint at a wider number of ecological niches in this environment compared to the relatively homogeneous marine system.